Proliferación de lubricadoras y lavadoras de vehículos y contaminación ambiental en la zona urbana de Calderón en el año 2012. diseño de un sistema de intervención. - Hidalgo Narváez, Simón Bolívar (2013)
The vehicle fleet in the Metropolitan District of Quito has shown constant growth in recent years, which implies a direct increase in the provision of services for the maintenance and operation of vehicles. The lubricating oil change and washing service are part of the daily activities of a mechanical workshop. Once their useful life has ended, these products become hazardous waste. Through some case studies, carried out in the community of Calderón, a diagnosis has been obtained that reflects the current management that each mechanical workshop provides for the hazardous waste in question. Then, as a result of the integration between the diagnosis obtained, the national legal framework and the compilation of national and international experiences existing to date, baselines are proposed to form an environmental management plan, under the concept of environmentally appropriate management.